Housing Price Determinants in Malaysia– in the Aspect of Macroeconomic Factors - Gan, Hwa Fern (2008)
Housing is widely connected to economy factors, and its complexity cause difficulties in prediction. Therefore it is essential to understand the mechanism underlying the housing market. This study suggests that fundamental macroeconomic factors, i.e. Gross Domestic Product, Lending Rate, Unemployment Rate, Construction Cost and Consumer Price Indices play important roles in determining the house prices. In this paper, econometric methodology has been adopted to study the relationship between housing price and fundamental macroeconomic factors in Malaysia for the period 1988 –2007. Vector Autoregressive (VAR) Model and Vector Error Correction (VEC) Model has been employed to examine the long term relationships and short run relationships between housing price and macroeconomic factors. The long run equilibrium shows that housing price is positively related to Consumer Price Indices but negatively related to other macroeconomic factors. The short run equilibrium shows the existence of long run influence from economic factors to house prices. Low coefficients of variables in the short run equilibrium indicates housing price is less elastic in responding to the changes of macroeconomic factors in short run. The relationships between house price and each macroeconomic factor are inspected through Granger causality test and generalised impulse response function. The results show that house price Granger causes Gross Domestic Product, Lending Rate, Construction Cost and Consumer Price Indices. According to the generalised impulse response analysis, Housing Price itself, Gross Domestic Product, Lending Rate and Construction Cost are highly sensitive to the changes of housing price